Dispute resolution in China: A test of black's theory of legal behavior - Kuai Mao; Yiwei Xia (PLoS ONE, 2026)
Since its introduction, Black’s theory of legal behavior (BBL) has been widely applied in empirical studies to analyze legal decision-making and dispute resolution. However, its applicability in non-Western contexts remains underexplored. This study examines the extent to which Black’s theory explains dispute resolution choices in China. Drawing on nationally representative data from the 2013 Chinese General Social Survey (CGSS), this research systematically investigates how five social dimensions—stratification, morphology, culture, organization, and alternative social control—shape individuals’ choices in resolving disputes. Conflict resolution strategies are categorized into four levels: silent endurance, direct communication, third-party mediation, and litigation. These categories are coded ordinally to reflect increasing degrees of the quantity of law involved. The findings indicate that while BBL offers a useful analytical framework, it does not fully account for all observed patterns. Some apparent alignments between the theory and empirical data may be influenced by challenges in operationalizing key social dimensions and the complex interactions among them. However, these deviations do not necessarily refute Black’s theory; rather, they highlight the need for further refinement in its application to diverse socio-legal contexts.